Effect of Patients Behavior and Family Health Companion Role on Hypertension Complication Occurrence (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2018)
ABSTRACT Various efforts of hypertension complications prevention have been carried out properly but the prevalence of hypertensive complications in NTT Province is still very high. The study aimed to determine the effect of patient behavior and family health companion role on the incidence of hypertension complications. The study was carried out in the work area of Sikumana Health Center in Kupang City with a case-control design. A total of 40 case samples and 40 control samples were taken by simple-random sampling. Data were analyzed by bivariate (simple logistic-regression) and multivariate (multiple-logistic regression), with significant values ​​of α <0.05 and OR> 1. The results showed that 70% of patients experienced Non-Hemorrhagic Stroke (SNH) complications and 30% experienced complications of Coronary Artery Disease (CAD). The results of the knowledge factor analysis (α=0.000, OR=4.775), attitude (α=0.998, OR=1.876), practice (α=0.000, OR=18.599), family health officer (α=0.000, OR=15.13) and simultaneously the practices of the patient (α=0.000, OR=17.233). There was a significant influence on patient knowledge, patient practices, and family health companion role on the incidence of hypertensive complications. The most influential variable was the patient's practices. Patients who had poor behavior had a risk of 17.233 times greater of complications of hypertension. Keywords : behavior of patients, family health companion role, complications of hypertension ABSTRAK Beragam upaya untuk mencegah komplikasi hipertensi, telah dilaksanakan dengan baik. Namun prevalensi komplikasi hipertensi di NTT masih sangat tinggi. Penelitian bertujuan untuk mengetahui pengaruh perilaku pasien dan peran pendamping kesehatan keluarga pada kejadian komplikasi hipertensi. Penelitian dilakukan di wilayah kerja Puskesmas Sikumana Kota Kupang dengan desain kasus-kontrol. Sebanyak 40 sampel kasus dan 40 sampel kontrol, diambil secara simple-random-sampling. Data dianalisis bivariat (regresi-logistic-sederhana) dan multivairiat (regresi-logistic-berganda), dengan nilai signifikan α<0,05 dan OR>1. Hasil penelitian menunjukkan 70% pasien mengalami komplikasi Stroke Non Haemoragik (SNH) dan 30% mengalami komplikasi Coronary Artery Diseases (CAD). Hasil analisis faktor pengetahuan (α=0,000, OR=4,775), sikap (α=0,998, OR=1876), tindakan (α=0,000, OR=18,599), peran pendamping kesehatan keluarga (α=0,000, OR=15,13), dan secara simultan tindakan pasien (α=0,000, OR=17,233). Ada pengaruh signifikan antara pengetahuan pasien, praktek/tindakan pasien, dan peran pendamping kesehatan keluarga terhadap kejadian komplikasi hipertensi. Variabel yang paling berpengaruh adalah praktek/tindakan pasien. Pasien yang memiliki praktek/tindakan kurang baik memiliki risiko 17,233 kali lebih besar terjadi komplikasi hipertensi. Kata Kunci : perilaku pasien, peran pendamping kesehatan keluarga, komplikasi hipertensi